Microstructure and properties of laser-clad FeNiCoCrTi0.5Nb0.5 high-entropy alloy coating. Issue 7 (2nd May 2020) - Zhang, Ying; Han, Tengfei; Xiao, Meng; Shen, Yifu
ABSTRACT: FeNiCoCrTi0.5 Nb0.5 high-entropy alloy coating is prepared on AISI 1045 steel by laser cladding. The cross-sectional macroscopic morphology, phase, microstructure, microhardness and wear resistance are studied systematically. The results show that FeNiCoCrTi0.5 Nb0.5 coating has no porosities, cracks or other defects and is well metallurgically bonded to the substrate. The coating is composed of body-centred cubic (BCC) solid solution, face-centred cubic (FCC) solid solution and hard Laves phase. The solid solution phase and Laves phase distribute uniformly and closely in a lamellar shape to form a fine and dense eutectic structure. The microhardness of FeNiCoCrTi0.5 Nb0.5 coating is about three times that of the substrate. Compared with the substrate, the coating has superior wear resistance.